Key Competencies of Built Environment Professionals for Achieving Net-Zero Carbon Emissions in the Ghanaian Construction Industry - Kofi Agyekum; Kezia Nana Yaa Serwaa Sackey; Felix Esahe Addoh; Hayford Pittri; John Sosu; Frederick Owusu Danso (Buildings)
The deficiency in competencies among built environment professionals (BEPs) in achieving sustainability goals presents a significant challenge, contributing substantially to the escalation of carbon emissions globally, with pronounced implications in Ghana. Addressing this issue is critical to bridging the existing knowledge gap concerning the role of key professional competencies in mitigating carbon emissions. This study, therefore, seeks to examine and synthesize the essential competencies required by BEPs to support the attainment of net-zero carbon emissions within the Ghanaian construction industry (GCI). A quantitative research approach was employed, utilizing a structured questionnaire survey to examine the opinions of 125 professionals, including architects, engineers, and construction managers. The questions were developed based on a review of the related literature. The data collected was analyzed using one-sample t-tests, multiple linear regression, and ANOVA to assess the significance and impact of the identified competencies on sustainability outcomes. The key competencies identified included “value engineering”, “stakeholder engagement for low-carbon development”, “circular impact assessment”, and “reverse logistics for sustainable material use”. This research also revealed the key competencies’ contributions to attaining environmental sustainability in the Ghanaian construction industry. Some key outcomes are “proper planning and provision of detailed net-zero carbon building specifications for contractors” and “promotion and implementation of net-zero carbon buildings”. It was identified that actions towards net-zero carbon emissions are the leading contributor to environmental sustainability, whereas the essential competencies have a greater impact on sustainable resource use. The findings highlight gaps in the current practices and underscore the need for improved professional training and development to meet sustainability goals. This study concludes that while professionals in the GCI are aware of sustainability objectives, significant improvements are needed in the application of sustainable practices.